2015
DOI: 10.1093/bjps/axu018
|View full text |Cite
|
Sign up to set email alerts
|

The Conventionality of Parastatistics

Abstract: Nature seems to be such that we can describe it accurately with quantum theories of bosons and fermions alone, without resort to parastatistics. This has been seen as a deep mystery: paraparticles make perfect physical sense, so why don't we see them in nature? We consider one potential answer: every paraparticle theory is physically equivalent to some theory of bosons or fermions, making the absence of paraparticles in our theories a matter of convention rather than a mysterious empirical discovery.We argue t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Moreover, interacting field theories and their superselection rules are far less well understood than free theories -this is a current generic problem with algebraic field theory. A good discussion of the equivalence of paraparticles and particles, together with the limitations of what is mathematically established, can be found in [4]. Thus, there is still some possibility of, as of yet unseen (c.f.…”
Section: 2mentioning
confidence: 99%
“…Moreover, interacting field theories and their superselection rules are far less well understood than free theories -this is a current generic problem with algebraic field theory. A good discussion of the equivalence of paraparticles and particles, together with the limitations of what is mathematically established, can be found in [4]. Thus, there is still some possibility of, as of yet unseen (c.f.…”
Section: 2mentioning
confidence: 99%
“…It was later demonstrated that this approach relates to the previous idea of parity deformed oscillators 3 , 6 8 characterized by a deformation parameter equivalent to the statistics order. Quantization of these parity deformed oscillators leads to interesting properties 9 12 but their selection rules render their natural occurrence highly unlikely 13 , 14 . Thus, a method for simulating these para-oscillators is most sought after.…”
Section: Introductionmentioning
confidence: 99%
“…Note that the standard boson algebra is recovered with order p = 1. Interestingly enough, quantum mechanics allows for the existence of paraparticles that have not been experimentally discovered as fundamental particles in nature [6,7]. On the other hand, trapped ions have proved a reliable platform for quantum simulation, offering high precision in both parameter control and measurement [8,9].…”
Section: Introductionmentioning
confidence: 99%